GENOTYPE-LOCATION INTERACTION OF INDICA RICE USING AMMI MODEL (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Phenotypic stability of 12 rice genotypes for plant height, days to maturity and yield were assessed at five different locations through regression and deviation from regression using Additive Main Effect and Multiplicative Interaction (AMMI) model. The result showed highly significant genotypic and G x E interaction. The G x E interaction influenced the relative ranking of the genotypes tested, BR1A/BR827R, Teea, BRRI dhan33 and Mayna showed low interaction effect with score nearest to zero with above average yield. While two genotypes BRRI hybrid dhan4 and Heera995 exhibited high positive interaction effect, gave mean grain yield around 5 ton/ha and was better suited to favorable environments. Similarly AMMI characterized the environments and identified Satkhira as a favorable environment for the better expression of the trait studied.DOI: http://dx.doi.org/10.3329/bjpbg.v24i2.17001